METODE PENCIPTAAN TARI KONTEMPORER “TUBUHKU, PUISI YANG BERGERAK” - Ali Sukri; Sahrul N (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
The creation of the concept for the performance My Body, Poetry That Moves is summed up from social reality. This concept is inseparable from the results of observations of the reality of the community where the phenomenon occurs. The results of the observations will be an important note for the creator. The observation results can be used as a basis and it can be concluded that in the era of modernization, with the rapid development of technology, it has positive and negative effects on the younger generation and society. On the positive side, the Indonesian nation has progress in the fields of communication and information, intellectual progress and thinking and so on. Meanwhile, the negative side of the Indonesian nation is unconsciously experiencing a tremendous setback, namely the erosion of morals, mentality, values which eventually becomes an instantaneous life. The process of creating My Body, Moving Poetry is carried out in several stages, namely contemplating the ideas presented and developed, rebuilding the empirical, reading various books as sources and supports in explaining concepts and observing the creation techniques. At the next level, the phenomenon captured is disclosed by pouring it into the form of body text which is expressed through the properties presented and contextual issues that contain message content. In the process of creating the artist, he pours out and marries the concept of contemporary body and choreography with a mix of local content and Minangkabau ideom.